The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.48550/arxiv.1306.3999
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Holographic Fluctuations from Unitary de Sitter Invariant Field Theory

Tom Banks,
Willy Fischler,
T. J. Torres
et al.

Abstract: We continue the study of inflationary fluctuations in Holographic Space Time models of inflation. We argue that the holographic theory of inflation [1] provides a physical context for what is often called dS/CFT. The holographic theory is a quantum theory which, in the limit of a large number of e-foldings, gives rise to a field theory on S 3 , which is the representation space for a unitary representation of SO(1, 4). This is not a conventional CFT, and we do not know the detailed non-perturbative axioms for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In [79] we showed the approximate SO(1, 4) invariance and the general rules of cosmological perturbation theory, including Maldacena's [80] squeezed limit theorem, was enough to reproduce the data. This general framework predicts a nearly scale invariant scalar two point function, and a small, equilateral scalar three point function, which is probably below the limits of near future observations.…”
Section: The Variables Satisfymentioning
confidence: 88%
“…In [79] we showed the approximate SO(1, 4) invariance and the general rules of cosmological perturbation theory, including Maldacena's [80] squeezed limit theorem, was enough to reproduce the data. This general framework predicts a nearly scale invariant scalar two point function, and a small, equilateral scalar three point function, which is probably below the limits of near future observations.…”
Section: The Variables Satisfymentioning
confidence: 88%
“…The gauge/gravity duality in the inflationary setup is discussed, e.g., in Refs. [3,4,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45].…”
Section: ζ Correlators From Holographymentioning
confidence: 99%
“…Work of Maldacena and others [14] has shown that current data on the CMB can be explained in a very simple framework, with no assumptions about particular models. Indeed, it was shown in [15] that the even the assumption that fluctuations originate from quantized fields is unnecessary. All one needs is the approximate SO(1, 4) invariance we will demonstrate below.…”
Section: So(1 4) Invariancementioning
confidence: 99%